Electron transport through a metallic nanoparticle assembly embedded in SiO2 and SiNx by low energy ion implantation. Issue 12 (10th September 2015) - Bayle, M.; Grisolia, J.; Ben Assayag, G.; Pecassou, B.; Bonafos, C.; Benzo, P.; Gourbilleau, F.; Carles, R.
Abstract: Original substrates have been developed to offer a new approach to modulate and analyse simultaneously electro‐optical and transport properties through an assembly of metallic nanoparticles (NPs). Using low energy ion implantation, silver NPs have been synthesized at the vicinity of the free surface of a SiO2 or SiNx matrix. Varying the parameters of the process allows us to modify the density of NPs and their distance to the surface. While Ag NPs surface fraction in SiO2 cannot exceed 20%, it reaches 30% in SiNx . In the latter case, NPs with mean diameter is about 2.1 nm have an interdistance compatible with tunnel effect. We then developed devices that electrically address the embedded assembly of NPs for I‐V characterization. The transport measurements on these devices show that an exploitable conduction is possible within the Ag NPs assembly in SiNx . The Arrhenius‐type temperature dependence model was successfully applied demonstrating that electron transport follows a simple thermally activated behaviour with the occurrence of a strongly localized regime. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)